2017
DOI: 10.1016/j.cortex.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Music and words in the visual cortex: The impact of musical expertise

Abstract: How does the human visual system accommodate expertise for two simultaneously acquired symbolic systems? We used fMRI to compare activations induced in the visual cortex by musical notation, written words and other classes of objects, in professional musicians and in musically naïve controls. First, irrespective of expertise, selective activations for music were posterior and lateral to activations for words in the left occipitotemporal cortex. This indicates that symbols characterized by different visual feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 68 publications
(64 reference statements)
2
27
0
1
Order By: Relevance
“…So the results suggest that music readers automatically recruit a specialized network of multimodal areas upon seeing musical notes. Using more complex musical-note sequences, the recruitment of V1/V2 was observed less consistently in some studies (Sergent, Zuck, Terriah, & MacDonald, 1992; Y. K. Wong & Gauthier, 2010) but not in others (Mongelli et al, 2016;Nakada, Fujii, Suzuki, & Kwee, 1998;Schön & Besson, 2002;Stewart et al, 2003), which might be related by the use of different types of visual control stimuli and tasks across studies. The selective engagement of both early and late visual areas associated with expertise has not been reported for object categories other than musical notes with the exception of written words in Szwed et al's (2011) fMRI study, in which V1/ V2, V3v/V4, and the visual word-form area were identified.…”
Section: Introductionmentioning
confidence: 86%
“…So the results suggest that music readers automatically recruit a specialized network of multimodal areas upon seeing musical notes. Using more complex musical-note sequences, the recruitment of V1/V2 was observed less consistently in some studies (Sergent, Zuck, Terriah, & MacDonald, 1992; Y. K. Wong & Gauthier, 2010) but not in others (Mongelli et al, 2016;Nakada, Fujii, Suzuki, & Kwee, 1998;Schön & Besson, 2002;Stewart et al, 2003), which might be related by the use of different types of visual control stimuli and tasks across studies. The selective engagement of both early and late visual areas associated with expertise has not been reported for object categories other than musical notes with the exception of written words in Szwed et al's (2011) fMRI study, in which V1/ V2, V3v/V4, and the visual word-form area were identified.…”
Section: Introductionmentioning
confidence: 86%
“…What is striking in humans, however, is that this mosaic of specialized regions is partially changed by the culture we live in. The acquisition of musical [ 6 ], mathematical [ 7 , 8 ], and reading abilities [ 9 ] leads to systematic changes in ventral visual organization.…”
Section: Introductionmentioning
confidence: 99%
“…As this relationship showed a trend ( p = 0.02), one should consider this finding with caution. The relationship between music and language has been investigated for decades as reflected, among others, in the elegant work of Patel [ 42 ] or Peretz [ 43 ]. Various studies have confirmed a relationship between music listening and language as they share similar capacities in terms of perception and processing as well as neuroanatomical markers in language aptitude and musicality [ 41 48 ].…”
Section: Discussionmentioning
confidence: 99%